Endogenous trade restrictions and exporters' pricing behaviour - Laura Rovegno (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
This paper analyses the effect of antidumping (AD) duties on the pricing behaviour of exporters targeted with these measures. Using product and firm-level data for South Korea, the study provides evidence of increased export unit values and firms' markups following the imposition of AD ad valorem duties. These findings are consistent with the hypothesis that, unlike other import tariffs, AD duties are not absorbed by exporters. The results on firms' average markups also suggest that the price adjustment following the imposition of AD duties occurs mostly through the export price, and not through reductions in the exporter's home price. The analysis controls for the presence of other trade measures as well as the endogeneity in AD and other contingent protection measures.
Keywords: F13; D22; D43; L11; 330; Endogenous trade policy; Import tariffs; Ad valorem duties; Antidumping; Markup; Unit values; Contingent protection